Historicity Muhammadiyah: What was the Idea of the Founder of Muhammadiyah as a â€œProgressive Islamic Movement?â€ - Darmayanti, Rani; Nurhakim, Moh.; Utsman, Yusuf Olawale Owa-Onire; Amien, Syaiful (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
This research aims to examine the historicity of KH Ahmad Dahlan, founder of Muhammadiyah, in emphasizing the theological principles of tajwid and ijtihad, describing the concept of development used by KH Ahmad Dahlan as an intellectual reaction to the social, political and economic challenges faced by Indonesian society during the Dutch colonial rule. This research uses systematic literature observation (SLR) methodology to identify, disseminate, and analyze all relevant research to answer research questions using the 7P technique. This research increases scientific knowledge about the Islamic reform movement, how insight into the theological principles it offers especially in the modern era, and how the concept of "Islamic Development" responds to the unique aspects of Globalization will be discussed in detail. The final results show the involvement of empowerment from the leaders of the Muhammadiyah movement to create effective educational and promotional initiatives to improve Islamic identity in society.Â Penelitian ini bertujuan untuk menguji historisitas KH Ahmad Dahlan, pendiri Muhammadiyah, dalam menekankan prinsip-prinsip teologis tajwid dan ijtihad, menggambarkan konsep pembangunan yang digunakan oleh KH Ahmad Dahlan sebagai reaksi intelektual terhadap tantangan sosial, politik dan ekonomi yang dihadapi oleh masyarakat Indonesia selama pemerintahan kolonial Belanda. Penelitian ini menggunakan metodologi systematic literature observation (SLR) untuk mengidentifikasi, menyebarluaskan, dan menganalisis semua penelitian yang relevan untuk menjawab pertanyaan penelitian dengan menggunakan teknik 7P. Penelitian ini meningkatkan pengetahuan ilmiah tentang gerakan reformasi Islam, bagaimana wawasan tentang prinsip-prinsip teologis yang ditawarkannya terutama di era modern, dan bagaimana konsep "Perkembangan Islam" menanggapi aspek-aspek unik Globalisasi akan dibahas secara rinci. Hasil akhir menunjukkan keterlibatan pemberdayaan dari para pemimpin gerakan Muhammadiyah untuk menciptakan inisiatif pendidikan dan promosi yang efektif untuk meningkatkan identitas Islam di masyarakat.